Experiencing living in God through uncreated divine energy - Petrov, George Daniel; Zagan, Andrei-Dragoș; Fofiu, Gheorghe Adrian (Technium Social Sciences Journal, 2022)
The transcendence of God requires that human spirituality seeks to experience it, through accessible, intelligible means, but constantly aware of the fact that the inexpressible cannot be expressed. The correct relation of the human to the divine transcendence is the foundation of what we call apophatic theology, the theology that defines God as being beyond the human capacity for knowledge.